Differential Relationships Between Diabetes Knowledge Scales and Diabetes Outcomes. (August 2017) - Dawson, Aprill Z.; Walker, Rebekah J.; Egede, Leonard E.
Background: Diabetes affects more than 29 million people in the US and requires daily self-management in addition to knowledge of the disease. Three knowledge assessments used are the Michigan Brief Diabetes Knowledge Test (DKT), Starr County Diabetes Knowledge Questionnaire (DKQ), and Kaiser DISTANCE Survey (DISTANCE). Purpose: The purpose of the study was to test the discriminate validity of 3 diabetes knowledge scales and determine which is best associated with diabetes self-care and glycemic control. Methods: Three hundred sixty-one adults with type 2 diabetes were recruited from primary care clinics. Four analyses were conducted to investigate the validity and relationships of the scale: alpha statistic to test internal validity, factor analysis to determine how much of the variance was explained, Pearson's correlation between the 3 scales, and Pearson's correlation between each scale, self-care, and outcomes. Results: The DKQ had an alpha of 0.75, the DKT had an alpha of 0.49, and DISTANCE had an alpha of 0.36. The DKQ was significantly correlated with glycemic control. The DKT scale was significantly associated with general diet, the DISTANCE survey was significantly associated with exercise, and both DKT and DISTANCE were significantly associated with foot care. Conclusion: Correlations among the 3 scales were modest, suggesting the scales are not measuring the same underlying construct. These findings indicate that researchers should carefully select scales appropriate for study goals or to appropriately capture the information being sought to inform practice.